3D PROPERTIES MODELING TO SUPPORT RESERVOIR CHARACTERISTICS OF W-ITB FIELD IN MADURA STRAIT AREA - Priatin Hadi Widjaja; D. Noeradi (BULLETIN OF THE MARINE GEOLOGY, 2010)
The gas field, initial named W-ITB Field, is located at the southwestern part of the East Java sedimentary basin in Madura Strait area. W-ITB Field was discovered by W-ITB#1 well in 2006. In W-ITB#1 well gas reservoir layer was just only found at Selorejo and Mundu Formation, on the other hand, on W- ITB#2 the gas reservoir is not found in Mundu Formation. Determination of reservoir characteristic including the distribution and quality at W-ITB Field, was done by using 3D geological modelling both for structure and stratigraphy. This model was executed based on integration of well data (petrophysics) and cross section seismic interpretation. The results, at Zone 2 and Zone 3 for vertical V-shale distribution shows as a good quality reservoir (0-15%). Laterally distribution, area at southwest of W-ITB 1 well has low V-shale or chatagorized as a good quality reservoir. While, porosity distribution, zone 1 and zone 2 have better reservoir (29-35% V-shale value) than Zones 3 and 4. NTG distribution result indicates that zone 2 and 3, with high value means a good reservoir. Due to only two exploration well, to guide lateral distribution, so that acoustic from seismic data is used for porosity distribution. Key words: modelling, reservoir, characteristic, V-shale, porosity, quality, Madura Strait Lapangan gas dengan nama inisial W-ITB terletak di bagian barat daya cekungan sedimen Jawa Timur yang termasuk di wilayah Selat Madura. Lapangan ini ditemukan dari Sumur W- ITB#1 pada tahun 2006. Pada sumur W- ITB#1 Lapisan reservoir yang mengandung gas hanya dijumpai pada Formasi Selorejo dan Mundu, namun dari hasil sumur W- ITB#2, lapisan reservoir gas dalam Formasi Mundu tidak diperoleh. Penentuan karakteristik reservoir termasuk distribusi dan kualitasnya di Lapangan W-ITB dilakukan dengan pemodelan geologi 3-Dimensi baik secara struktur dan stratigrafi dengan berdasarkan pada integrasi data sumur pemboran dan penampang seismik yaitu analisis petrofisik dan interpretasi seismik. Berdasarkan pemodelan 3-Dimensi, pada Zone-2 dan Zone-3 untuk distribusi V-shale secara vertikal merupakan zone dengan kandungan reservoir yang baik dengan nilai V-sh 0 – 15%. ecara distribusi lateral, wilayah di bagian barat daya dari sumur W- ITB#1 memiliki kandungan V-sh yang rendah atau dikategorikan reservoir dengan kualitas baik. Adapun pada distribusi porositas, Zona-1 dan Zona-2 mengandung reservoir yang lebih baik dengan nilai 29- 35% daripada Zona-3 dan Zona-4. Hasil distribusi NTG mengindikasikan bahwa Zona-2 dan Zona-3 dengan nilai tinggi mengandung reservoir yang baik. Karena hanya memilki dua sumur eksplorasi, untuk memandu distribusi lateral maka hasil impedansi akustik dari data seismik digunakan untuk distribusi porositas. Kata kunci: pemodelan, reservoir, karakteristik, V-serpih, porositas, kualitas, Selat Madura